2021
DOI: 10.3389/fcell.2021.690502
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Melatonin and Zoledronic Acid Suppressed the Giant Cell Tumor of Bone in vitro and in vivo

Abstract: Melatonin (Mlt) confers potential antitumor effects in various types of cancer. However, to the best of our knowledge, the role of Mlt in the giant cell tumor of bone (GCTB) remains unknown. Moreover, further research is required to assess whether Mlt can enhance the therapeutic effect of zoledronic acid (Zol), a commonly used anti-GCTB drug. In this research, we investigated the effects of Mlt, Zol, and the combination of these two drugs on GCTB cells’ characteristics, including cell proliferation, apoptosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In difficult-to-treat GCTBs conservative approaches have been conceptualized on the basis of breaking the vicious cycle established at the TME level in GCTB [5] , [12] . BPs like ZA are, besides their osteoclast inhibitory effects, believed to impair tumour growth by targeting both cellular components, MNGCs, and mutated H3F3A G34W + cells [18] , [19] , [20] , [21] , [22] , [23] , while RANKL inhibitors suppress only the osteoclastogenesis with limited direct effects on tumour cells [3] , [22] , [24] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In difficult-to-treat GCTBs conservative approaches have been conceptualized on the basis of breaking the vicious cycle established at the TME level in GCTB [5] , [12] . BPs like ZA are, besides their osteoclast inhibitory effects, believed to impair tumour growth by targeting both cellular components, MNGCs, and mutated H3F3A G34W + cells [18] , [19] , [20] , [21] , [22] , [23] , while RANKL inhibitors suppress only the osteoclastogenesis with limited direct effects on tumour cells [3] , [22] , [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In different in-vitro and animal studies, it was demonstrated that nitrogen-containing BPs did cause substantial apoptotic effect in GCTB stromal cells [25] , [26] , [29] . This effect can be enhanced by melatonin, which acts synergistically with ZA [23] . Using flow cytometry following fluorescent Annexin-V labeling, it was observed that statistically significant increase of tumour cell apoptosis in GCTB primary cultures started at 30 µM of ZA or PAM with maximal effects at 150 µM [29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation